MOTIVASI DOSEN EKONOMI DALAM MENINGKATKAN KINERJA PUBLIKASI PENELITIAN: INVESTIGASI PENERAPAN NACH THEORY - Kemal Budi Mulyono (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
This study aims to analyze the three dimensions of Achievement Motivation Nach Theory McCleland works in encouraging the performance of research publications. The data in this study were obtained from a closed questionnaire with a scale of 1-7 agree-disagree intervals with the unit of analysis for Lecturers at the Faculty of Economics, Universitas Negeri Semarang. This study was analyzed by (1) descriptive analysis, through a description of the percentage of each variable; (2) as well as inferential analysis through Structural Equation Modeling analysis of single equations using the bootstrapping method. The results of this study indicate that the need for power does not affect the performance of research publications, meanwhile, the need for achievement and the need for affiliation affect the performance of research publications. Therefore, the implications of this study indicate that the faculty management can increase the need for affiliation and the need for achievement based on the study center by increasing funding.